A Prospective Randomized Controlled Study of Oral Tranexamic Acid for the Prevention of Postinflammatory Hyperpigmentation After Q-Switched 532-nm Nd:YAG Laser for Solar Lentigines - Suthinee Rutnin (2020)
© 2019 Wiley Periodicals, Inc. Background and Objectives: Q-switched (QS) 532-nm Nd:YAG laser is one of the treatment options for solar lentigines (SLs). However, the high incidence of postinflammatory hyperpigmentation (PIH) is concerning, especially in dark-complexioned skin. Tranexamic acid (TA) can decrease melanogenesis and has been used to treat melasma. The aim of this study is to evaluate the efficacy and safety of oral TA for PIH prevention and clearance in patients with SL treated with QS 532-nm Nd:YAG laser. Study Design/Materials and Methods: Forty patients with SL treated with QS 532-nm Nd:YAG laser were enrolled in this randomized controlled trial. They were randomly assigned to be receive oral TA 1,500 mg daily or placebo for 6 weeks. Results were evaluated by blinded investigators using digital photographs, dermatoscopy, colorimetry, physician grading scores, and patient satisfaction scores at baseline, 2nd, 4th, 6th, and 12th weeks. Results: The incidence of PIH, relative melanin value, lightness index, and clinical improvement scores were not significantly different between the two groups. However, the TA group had a significantly lower incidence of dermatoscopic finding of pigmented granules, which correspond to PIH at 6th and 12th weeks (P = 0.038 and 0.013, respectively). Homogenous light brown pigmentation under dermatoscopy was significantly associated with higher clinical improvement. Conclusions: Oral TA therapy starting at the first day postlaser treatment is not effective for PIH prevention after QS 532-nm Nd:YAG laser in SL. However, PIH clearance, as assessed dermatoscopically, is significantly improved by oral TA at 6th and 12th week. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.